Factors Influencing Mental Health Literacy in Indian Tribal Communities - Ehsas Kakkar; Paramita Bhattacharya; Nirmalaya Mukherjee; Subhash Pokhrel (BJPsych Open, 2025)
Aims: About 9% of India’s population is made up of tribal communities consisting 120 million people nationwide. The mental health literacy of these communities is an unexplored topic. This literature review is aimed to identify and summarise existing factors that influence mental health literacy of the tribal communities in India and use this information to develop a survey questionnaire to support the development of a community radio programme.